Implementing honeypots to fight spammers / Mohd Saiful Abd Talib - Abd Talib, Mohd Saiful (2005)
Spam can be considered as unwanted email. Those emails usually contain advertisements that can found in postal mailboxes. Although spam generally not considered as real cyber attack, it may be difficult to differentiate between viruscontaminated emails. Moreover, spammers slow the servers that receiving legitimate emails and may cause availability problems. Typical solutions against this problem may be to filter emails received by using content analysis or blacklists. Hence this project discusses the usefulness of using homemade honeypots to fight spammers. Sendmail is used in this project as a decoy to fool spammers. This paper will explain how typical spammers work, as well as how honeypots could be used to detect spammers, slow spammers, and stop spammers from such activities.